Precoder design for cognitive high throughput satellite networks - Chua, Clement Jun Hao (2018)
Satellite communication systems which make used of Geosynchronous satellites for transmissions suffers from delays due to the large distances between transmission and this is one major concern in terms of time critical transmission. In this project we investigate a proposed solution of incorporating an Unmanned Aerial Vehicle (UAV) into our traditional satellite system. Also, in the project we aimed to find out the effects of incorporating the UAV through the verification of Bit Error Rate(BER), the design of the precoding of transmitting signals and the design of the communication system model. Three main precoding techniques that we investigated includes Zero-Forcing (ZF) precoding, Regularized Zero-Forcing (RZF) and Dirty Paper Coding (DPC) but more emphasis is placed on ZF precoding. Our communication system model is also extended to a Dual Satellite System which incorporates Cooperative Precoding (CP) and Interference Ignorance (II) at the ground receivers to further enhance the performance. In this project, MATLAB software is used as our main integrated development enviornment(IDE) for coding and plotting of graphical results for our simulations. At the end of this project, we are able to obtain satisfactory positive BER results which shows the effects of not only by incorporating UAV to the satellite system, but also considering Dual Satellite System which includes CP and II.